Os desvios da consciência e a crise dos experimentalismos - Ronaldo Lima Lins (Ciências Sociais Unisinos)
The present culture, the systems of consciousness and its connections with the deadlocks of our times. The study of the anatomy of the shadows in the formulation of a critical thought. The crises of experimentalisms in the expressions of post-modern art. The need to develop new forms of reading the present trends of literature